2003
DOI: 10.1080/08035250310003938
|View full text |Cite
|
Sign up to set email alerts
|

Acute intermittent porphyria in childhood: a population-based study

Abstract: AIP symptoms in children may be vague and of short duration and U-ALA and U-PBG levels are often elevated only slightly or not at all; thus, symptoms and signs may differ from those in adults. Children of AIP gene carriers should be DNA tested, followed up and carefully instructed on preventive measures to avoid developing manifest AIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…His younger sister shows normal urinary excretion of haem precursors and a porphobilinogen deaminase activity in an intermediate range (Table 2). This result agrees with the finding that the levels of urinary porphyrin precursors in children are often only slightly elevated or that there is no elevation (Hultdin et al 2003). For such individuals a molecular investigation could help to elucidate the situation (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…His younger sister shows normal urinary excretion of haem precursors and a porphobilinogen deaminase activity in an intermediate range (Table 2). This result agrees with the finding that the levels of urinary porphyrin precursors in children are often only slightly elevated or that there is no elevation (Hultdin et al 2003). For such individuals a molecular investigation could help to elucidate the situation (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Paralysis and respiratory failure are rare but potentially lethal complications, highlighting the need for early diagnosis (Herrick and McColl 2004). Symptoms very rarely develop before puberty, but there exists a few documented cases of AIP in children (Sandberg et al 2001;Elder 1997;Hultin et al 2003).…”
Section: Acute Intermittent Porphyriamentioning
confidence: 99%
“…Hultdin et al reported 61 Swedish children (<18 years) with confirmed HMBS mutations followed prospectively for an average of 2.5 years. Based on their study, approximately 10% of these children (3 boys and 3 girls) developed clinical evidence of an acute attack before age 15 [10]. …”
Section: Reviewmentioning
confidence: 99%